PROTOZOA EKTOPARASITIK PADA IKAN KOI Cyprinus carpio DI DAERAH SUKABUMI - Amalia Putri Firdausi; Rahman Rahman; Respati Mahadhika; Adna Sumadikarta (Jurnal Akuakultur Rawa Indonesia, 2020)
The aim of this study is to inventory various types of ectoparasites found in koi fish that are reared in the nursery phase at the Sukabumi Freshwater Aquaculture Center (BPAT Sukabumi). Briefly, a total of 30 koi fish were taken randomly, then the scales, fins, and gills were examined and stained either with procedures of AgNO3. The type of parasite was identified and analyzed based on the rate of prevalence, also the intensity and dominance. The infesting parasite found were Trichodina sp, Oodinium sp, and Ichthyophthirius multifiliis. Overall, Trichodina sp is the most dominating parasite with a dominance level, prevalence, and intensity of 57,028%, 80%, and 10,833 respectively.